2010
DOI: 10.1007/s10750-010-0225-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of El Niño-driven environmental variability on black turtle migration to Peruvian foraging grounds

Abstract: We analyzed sea temperature as an environmental factor, in association with ENSO, affecting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 36 publications
1
27
0
2
Order By: Relevance
“…In general, sea turtles fast during the internesting period due to the lack of food availability in the breeding areas (Hays et al 2000), but some populations do feed during the nesting season (Hochscheid et al 1999;Tucker & Read 2001). Even though there was no seagrass and few algae were present on the bottom in the area near the nesting beach (Reina et al 2005;Bernecker & Wehrtmann 2009), our green turtles could have been consuming invertebrates (Amorocho & Reina 2007;Quiñones et al 2010). As a result, and because we could not observe turtles in the water, we cannot rule out foraging behavior.…”
Section: Diving Behaviormentioning
confidence: 98%
See 1 more Smart Citation
“…In general, sea turtles fast during the internesting period due to the lack of food availability in the breeding areas (Hays et al 2000), but some populations do feed during the nesting season (Hochscheid et al 1999;Tucker & Read 2001). Even though there was no seagrass and few algae were present on the bottom in the area near the nesting beach (Reina et al 2005;Bernecker & Wehrtmann 2009), our green turtles could have been consuming invertebrates (Amorocho & Reina 2007;Quiñones et al 2010). As a result, and because we could not observe turtles in the water, we cannot rule out foraging behavior.…”
Section: Diving Behaviormentioning
confidence: 98%
“…East Pacific green turtles are present from San Diego Bay to Peru (Green 1984;Quiñones et al 2010). Little is known about green turtle breeding populations in the eastern Pacific.…”
Section: Introductionmentioning
confidence: 99%
“…Each replicate is a unique combination of species, life history stage, date and location and is therefore analysed separately within the model. The sample size of the studies ranged from a minimum of seven turtles (Seminoff et al, 2002a) to a maximum of 192 turtles (Quinones et al, 2010). The debris levels for the replicates incorporated in the model covered a wide spread of the predicted global debris levels (Fig.…”
Section: Consequence (Necropsy Data)mentioning
confidence: 99%
“…Even terrestrial plant material, especially mangrove leaves and propagules (or seeds), can feature prominently in green turtle diets (Arthur et al 2009;Limpus and Limpus 2000;Nagaoka et al 2012). Contrary to the long-held belief that green turtles are strictly herbivorous, however, animal matter ranging from accidentally ingested small hydrozoans and bryozoans that encrust plant material to purposefully consumed sponges (Mortimer 1981) and significant amounts of gelatinous macrozooplankton (e.g., Amorocho and Reina 2007;Burkholder et al 2011;Fukuoka et al 2019;González Carman et al 2014;Quiñones et al 2010) have been reported in the diet of both juvenile and adult green turtles.…”
Section: Introductionmentioning
confidence: 99%